(untitled) (Proceedings of the International Conference on Public Health, 2021)
Schools regularly collect student health data. School health is organized to improve the ability of students to live healthy so that students can learn, grow, and develop in harmony and become quality human resources. In Indonesia, school health priorities are included in the 3rd National MediumTerm Development Plan strategy. However, in Indonesia students, health data is underutilized because data documentation on paper causing some difficulties in terms of storage, use for monitoring and further analysis. The participation and involvement of parents, schools and community health centers in monitoring the health status of students today is still very limited due to the lack of information that can be accessed easily. Objectives: To design a student health record application model that can display student health examination results and connect the data to community health centers, schools and parents in real time. Method: Designing student health record application model with the context diagram, Entity Relationship Diagram (ERD), Table Relational Diagram (TRD), and user interface input and output. Results: The results of this study are a comprehensive student health record system model. The student health record will be applied in the form of mobile devices used by students and parents, which are connected to schools and community health centers by web-based platform. Conclusions: The student health record application model shows a systematic solution that is user friendly, immediately captures data, displays the dashboard in real time, directly connects to parents, schools and community health centers. All of this in the future if implemented properly can early detect student health problems and monitor the health status of students.